Internet connectivity disruption in Canada (Canada) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity disruption detected in Canada. Data sourced from IODA.
Network Disruption Incident ID: CA-2026-0015. Severity: critical. Confidence: 65%